The effects of Crataegus aronia var. dentata Browicz extract on biochemical indices and apoptosis in partially hepatectomized liver in rats - Nazan Keskin; Ramazan Mammadov; Pinar Ili (Biomolecules & Biomedicine, 2012)
Crataegus species have been widely used in herbal medicine, especially for the hearth diseases. In the present study, the effect of Crataegus aronia var. dentata Browicz extract on partially hepatectomized rats was investigated with biochemical and TUNEL apoptosis assays. The extracts of the plant at the concentrations of 0.5 and 1 ml/100 g body weight/day were administered orally to the two experimental groups including partially hepatectomized rats for 42 days. At the end of the experimental period, animals were sacrificed, blood was collected for the assessment of serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyltransferase (GGT), and the liver tissue was used for TUNEL assay.